Unregulated health care workers in the care of aging populations: Similarities and differences between Brazil and Canada. Issue 1 (1st January 2016) - Veras, Mirella; Paquet, Nicole; Oliveira, Eliany N.; Zakus, David; Deonandan, Raywat; Pottie, Kevin
Abstract : Introduction: The world's population is rapidly aging. Unregulated health care workers (UHCWs) are emerging as a potentially important workforce in the care of older adults. Objective: A review was conducted to identify the activities of UHCWs with respect to contributions and limitations. Methods: A systematic integrative literature review was conducted using online databases (LILACS, PubMed, EMBASE, CINAHL, and grey literature). The inclusion criteria were as follows: (i) description of UHCW activities related to older adults; and (ii) description of UHCW activities performed in Brazil or Canada. Results: Eleven papers were included in this review. In both countries, UHCW activities included health promotion, mental health care, and rehabilitation. In Brazil, UHCWs performed integrated care, while in Canada UHCWs performed personal care and housekeeping. Conclusion: These results highlight the potential and limits of UHCWs who provide care for the aging population. Such information is important to health and social policy making and household decision making.